2022
DOI: 10.1111/apm.13207
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of chemiluminescent immunoassay and enzyme‐linked immunosorbent assays for the diagnosis of West Nile virus infections

Abstract: In August 2020, anew West Nile virus (WNV) outbreak affected 71 people with meningoencephalitis in Andalusia (Spain). Samples from these individuals were received in our laboratory, a regional Virus Referral Centre. The aim of this study was to compare the agreement, sensitivity and specificity of findings between the WNV VIRCLIA IgG and IgM assay (Vircell, Spain) and the WNV ELISA IgM and IgG assay (Euroimmun, Germany) and to compare the performance of WNV VIRCLIA IgM and Euroimmun ELISA for cerebrospinal flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A specificity of 95% was calculated by Beck et al [17]; excellent sensitivity and specificity values of cELISA were also reported in [34]. Gómez-Vicente et al [35] even found 100% specificity for IgG-ELISA when comparing its diagnostic capabilities against chemiluminiscent immunoassay in human serum samples. The differences between the two assays are probably due to cross-reactivity with other unstudied flaviviruses in Bulgaria or due to the high sensitivity of ELISA in the detection of antibodies against glycoprotein E in the early stages of infection, which are non-neutralizing.…”
Section: Discussionmentioning
confidence: 88%
“…A specificity of 95% was calculated by Beck et al [17]; excellent sensitivity and specificity values of cELISA were also reported in [34]. Gómez-Vicente et al [35] even found 100% specificity for IgG-ELISA when comparing its diagnostic capabilities against chemiluminiscent immunoassay in human serum samples. The differences between the two assays are probably due to cross-reactivity with other unstudied flaviviruses in Bulgaria or due to the high sensitivity of ELISA in the detection of antibodies against glycoprotein E in the early stages of infection, which are non-neutralizing.…”
Section: Discussionmentioning
confidence: 88%
“…The primary advantage of CLIA is its wide dynamic range, which may aid in setting appropriate test cut-offs [111]. Currently, CLIA has been found to be very useful for laboratory diagnosis of HIV, hepatitis B [112], adenovirus [113], HCV, syphilis [114], T. gondii [115], Varicella Zoster [116], and West Nile virus [117].…”
Section: Chemiluminescence Immunoassaysmentioning
confidence: 99%
“…However, its reported cross-reactivity with DENV is as high as 95% and ranges from 30.0-57.1% for other flaviviruses such as JEV, YFV, and the St. Louis encephalitis virus (SLEV) [73]. The Euroimmun kit, on the other hand, has a reported sensitivity of 91.1% and a specificity of 100.0% according to one study that used patient samples [74]. It is also reported to have low cross-reactivity to other flaviviruses [75].…”
Section: Igg Elisas Used In Flavivirus Serosurveysmentioning
confidence: 99%